UPAYA PENINGKATAN KUALITAS PRODUKSI PREFORM DENGAN METODE SIX SIGMA DI PT.KAS - feri alifianto (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
KAS is a company which moving in the packaging area with various types of packaging, such as 140 ml preform, 265 ml, and 625 ml. The problem that often showed is the decrease of product quality, so that technique is needed to improve the quality of existing product. To improve the product was conducted the observations on 140 ml preform for about 8 months. The percentage of 140 ml preform defect was greater than 265 ml and 625 ml of preform defect at 9.54%. Hopeto know the stages, the value of DPMO, factors that occur from the decline quality and the proposed improvement. In facilitating the completion of quality improvement, it needs to be a “Six Sigma” method with DMAI. “Six Sigma” is a high-disciplinary process that helps us to develop and deliver near-perfect products. “Six Sigma” is a quality target with a value of 3.4 DPMO (Defect per Million Oppurtunity) or 3.4 defects from the per-millions opportunity. The achievement of the “six sigma” 3.4 DPMO is said to be realistic to be achieved from a quality based on zero defect. Reduction in the disability quantity in research using six sigma method with DMAI (Define, Measure, Analize, Improve). From the analysis result and research that has been done with the number of disability products at PT. KAS is at the level of sigma value 3.12 with DPMO of 52,831.12. From this it can be defined that the product quality is still far from the 6 sigma product level. By using the analysis tool diagram can be able to know the cause of product damaged in the production process that comes from human, machine, finance, motivation, and material. Able to know the concept of completion of quality improvement with the Define, Measure, Analysis, Improve method,doinga plan of improvement on thickness of defect, cracked, striped, chipped and bubbly.